THE IMPLEMENTATION OF PROJECT BASED LEARNING USING CAPCUT TO IMPROVE STUDENTS' SPEAKING SKILLS OF EIGHTH-GRADE AT SMP NEGERI 5 SURADE - Usman Diennur; Aris Setiawan Muhammad; Seli Mutiara; Rahayu Lestari; M Rayiz Ayinul Mutaqin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aimed to determine the effectiveness of the implementation of Project-Based Learning using CapCut in improving the speaking skills of eighth-grade students at SMP Negeri 5 Surade. Students still experienced several difficulties in speaking English, such as limited vocabulary, lack of confidence, incorrect pronunciation, and low speaking fluency. To overcome these problems, Project-Based Learning integrated with CapCut through advertisement video projects was implemented as an alternative learning strategy. This research employed a quantitative approach using a pre-experimental method with a one-group pre-test and post-test design. The subjects of this research were 20 students of class VIII A at SMP Negeri 5 Surade. The data were collected through speaking tests assessing pronunciation, grammar, vocabulary, fluency, and comprehension. The findings of the research showed that the students’ speaking skills improved significantly after the treatment. The students’ mean score increased from 47.8 in the pre-test to 68 in the post-test. In addition, the paired sample t-test showed a significance value of 0.000, which was lower than 0.05. The result indicated that there was a significant difference between students’ speaking skills before and after the implementation of Project-Based Learning using CapCut. Therefore, it can be concluded that Project-Based Learning integrated with CapCut was effective in improving students’ speaking skills.